More Environmental Sustainability Routing and Energy Management for All Electric Ships - Pan, Xuewei; Zhu, Xingzhou; Zhao, Fei (Frontiers in Energy Research, 2022)
As the popularity of electrification of marine transportation, the strategic energy-saving and environmental-friendly management gains more attention recently. This paper proposes a coordinated navigation routing and power generation scheduling model, which aims at making a compromise between total operation cost and greenhouse gas emissions under practical operation constraints of ship. A novel maritime hybrid energy configuration that combines diesel generator (DG), battery energy storage system (BESS), fuel cell (FC), photovoltaic (PV) and cold-ironing connection is presented with a real-world navigation routine from Dalian to Singapore, and the optimization problem is solved through a bi-level multi-objective differential evolution algorithm (MODEA), where navigation parameters, hybrid-ESS capacity and weight between contradictory objective functions are optimized in the upper level and specific power generation scheduling is settled in the lower level. Six case studies are conducted to verify its effectiveness and accuracy, and the simulation results demonstrate the proposed method can further reduce the operation cost while minimizing air contamination.